The hornworts: morphology, evolution and development. Issue 2 (15th September 2020) - Frangedakis, Eftychios; Shimamura, Masaki; Villarreal, Juan Carlos; Li, Fay‐Wei; Tomaselli, Marta; Waller, Manuel; Sakakibara, Keiko; Renzaglia, Karen S.; Szövényi, Péter
Summary: Extant land plants consist of two deeply divergent groups, tracheophytes and bryophytes, which shared a common ancestor some 500 million years ago. While information about vascular plants and the two of the three lineages of bryophytes, the mosses and liverworts, is steadily accumulating, the biology of hornworts remains poorly explored. Yet, as the sister group to liverworts and mosses, hornworts are critical in understanding the evolution of key land plant traits. Until recently, there was no hornwort model species amenable to systematic experimental investigation, which hampered detailed insight into the molecular biology and genetics of this unique group of land plants. The emerging hornwort model species, Anthoceros agrestis, is instrumental in our efforts to better understand not only hornwort biology but also fundamental questions of land plant evolution. To this end, here we provide an overview of hornwort biology and current research on the model plant A . agrestis to highlight its potential in answering key questions of land plant biology and evolution.